Desiccation tolerance in plants: Structural characterization of the cell wall hemicellulosic polysaccharides in three Selaginella species. (15th March 2019) - Plancot, Barbara; Gügi, Bruno; Mollet, Jean-Claude; Loutelier-Bourhis, Corinne; Ramasandra Govind, Sharathchandra; Lerouge, Patrice; Follet-Gueye, Marie-Laure; Vicré, Maïté; Alfonso, Carlos; Nguema-Ona, Eric; Bardor, Muriel; Driouich, Azeddine
Highlights: Comparative structural characterization of leaf cell walls of desiccation-tolerant and desiccation-sensitive Selaginella species. Leaf cell walls Selaginella species are mainly composed of hemicellulosic polysaccharides namely arabinoxylan, mannan and xyloglucan. Desiccation induces significant structural alterations of the xyloglucan and arabinoxylan in S. involvens compared to S. kraussiana and S. moellendorffii . Structural remodeling of these hemicellulosic polysaccharides is an important process leading to desiccation tolerance in Selaginella plants. Abstract: Drought-induced dehydration of vegetative tissues in lycopods affects growth and survival. Different species of Selaginella have evolved a series of specialized mechanisms to tolerate desiccation in vegetative tissues in response to water stress. In the present study, we report on the structural characterization of the leaf cell wall of the desiccation-tolerant species S. involvens and two desiccation-sensitive species, namely S. kraussiana and S. moellendorffii . Isolated cell walls from hydrated and desiccated leaves of each species were fractionated and the resulting oligosaccharide fragments were analyzed to determine their structural features. Our results demonstrate that desiccation induces substantial modifications in the cell wall composition and structure. Altogether, these data highlight the fact that structural remodeling of cell wall hemicellulosic polysaccharides including XXXG-rich xyloglucan, arabinoxylan and acetylated galactomannan is an important process in order to mitigate desiccation stress in Selaginella .